Flowering Characteristics and Expression Patterns of Key Genes in Response to Photoperiod in Different Chrysanthemum Varieties - Qiuling Zhang; Xueru Li; Shuyu Cai; Junzhuo Li; Jiaying Wang; Yanfei Li; Silan Dai (Horticulturae)
Chrysanthemum × morifolium Ramat. is a globally renowned ornamental flower. It includes numerous varieties, most of which are typical short-day (SD) plants, and the flowering characteristics of different chrysanthemum varieties in response to the photoperiod vary greatly. In this study, seven representative chrysanthemum varieties were selected for a comparative analysis of flowering traits under long-day conditions (16 h/8 h day/night) and short-day conditions (12 h/12 h day/night). It was found that three varieties (‘A44’, ‘C60’, and ‘183’) belonged to obligatory short-day varieties and four varieties (‘A20’, ‘C1’, ‘C27’, and ‘C31’) belonged to facultative short-day varieties. The short-day conditions not only induced earlier flowering but also improved flowering quality in the facultative SD varieties. Different chrysanthemum varieties required different light conditions to complete the vegetative stage and reach the floral competent state. Seven chrysanthemum varieties, ‘A44’, ‘C60’, ‘183’, ‘A20’, ‘C1’, ‘C27’, and ‘C31’, reached a floral competent state in the L20, L20, L22, L22, L18, L20, and L24 periods, respectively, and were most sensitive to SD induction at this time. The expression patterns of key floral genes in the photoperiod pathway were analyzed and it was found that CmCRY1, CmCRY2, CmGI1, CmGI2, and CmCO were mainly expressed in leaves. Then, comparing the expression levels of these genes under LD and SD conditions, the expression of CmGI1, CmGI2, CmCO, and CmFTL were not significantly induced in the obligatory SD varieties, while the expression of them in the facultative SD varieties were induced by SD conditions. This may be the reason why the facultative varieties could respond to SD conditions more quickly to complete the floral transition. In addition, SD induction under different photoperiodic conditions and growth states resulted in differences in the phenotype of flowering. This result provides guidance for the artificial regulation of chrysanthemum flowering and improvement of ornamental quality, as well as clues for analyzing the flowering mechanism of chrysanthemums under different photoperiod conditions.